The Impact of Nosocomial Bloodstream Infections on Mortality: A Retrospective Propensity-Matched Cohort Study. (6th November 2021) - Petersiel, Neta; Sherman, Assa; Paul, Mical
Abstract: Background: The mortality toll of nosocomial infections drives infection control efforts. We aimed to assess the contemporary mortality associated with nosocomial bloodstream infections (BSIs). Methods: Retrospective propensity-matched cohort study conducted in 1 hospital in Israel between January 2010–December 2020. Adults >18 years old with nosocomial BSI were matched to controls using nearest neighbor matching of the propensity score for nosocomial BSI. We assessed all-cause mortality at 30 days, 90 days, and survival up to 1 year starting on the BSI day or matched hospital-day among controls; and the functional and cognitive change between admission and discharge using the Norton score among patients discharged alive. Residual differences between matched groups were addressed through Cox regression for 1-year survival. Results: A total of 1361 patients with nosocomial BSI were matched to 1361 patients without BSI. Matching achieved similar patient groups, with small differences remaining in the Charlson score and albumin and hemoglobin levels. At 90 days, mortality was higher among patients with BSI (odds ratio [OR], 3.36 [95% confidence interval CI, 2.77–4.07]). ORs were higher when the BSI was caused by multidrug-resistant bacteria (OR, 5.22 [95% CI, 3.3–8.26]) and with inappropriate empirical antibiotics in the first 24 hours (OR, 3.85 [95% CI, 2.99–4.94]). Following full adjustment, the hazard ratio for 1-year mortality with nosocomial BSI was 2.28 (95% CI, 1.98–2.62). The Norton score declined more frequently among patients with BSI (OR, 2.27 [95% CI, 1.81–2.86]). Conclusions: Nosocomial BSIs incur a highly significant mortality toll, particularly when caused by multidrug-resistant bacteria. Among hospital survivors, BSIs are associated with functional decline. Abstract : In a propensity-matched cohort study, the hazard for death with a follow-up of 1 year following non–intensive care unit nosocomial bacteremia was more than double that of matched patients without bloodstream infection.